18F-FDG—PET/CT in Canine Mammary Gland Tumors - Sánchez, Diana; Romero, Laura; López, Sergio; Campuzano, Margarita; Ortega, Rocio; Morales, Alfonso; Guadarrama, Marina; Cesarman-Maus, Gabriela; García-Pérez, Osvaldo; Lizano, Marcela (Frontiers in Veterinary Science, 2019)
Medical imaging techniques play a central role in clinical oncology, helping to obtain important information about the extent of disease, and plan treatment. Advanced imaging modalities such as Positron Emission Tomography–Computed Tomography (PET/CT), may help in the whole-body staging in a single procedure, although the lesions should be carefully interpreted. PET/CT is becoming commonly used in canine cancer patients, but there is still limited information available on specific tumors such as mammary cancer. We evaluated the utility of fluorine-18 fluorodeoxyglucose (18F-FDG)-PET/CT to detect malignant lesions in eight female dogs with naturally occurring mammary tumors. A whole-body scan was performed prior to surgery, and mammary and non-mammary lesions detected either on PET/CT or during pre-surgical physical exam were resected when possible and submitted for histopathological examination. Multiple mammary lesions involving different mammary glands were detected in 5/8 dogs, for a total of 23 lesions; there were 11 non-mammary-located lesions in 6/8 dogs, three of these were lung or lymph node metastasis. A total of 34 lesions were analyzed: 22 malignant (19 mammary tumors and three metastatic lesions), and 12 benign (four mammary lesions and eight of non-mammary tissues). Glucose uptake by maximum standardized uptake value (SUVmax) was analyzed and correlated with tumor size, and benign vs. malignant pathology. We found that the minimum tumor size needed to distinguish malignant lesions according to the SUVmax was 1.5 cm; benign and malignant lesions <1.5 cm did not differ in glucose uptake (mean SUVmax = 1.1). In addition, a SUVmax value >2 was 100% sensitive for malignancy. Combining these data, lesions >1.5 cm with a SUVmax >2 had a positive predictive value of 100%. Finally, we did not find an association between SUVmax and histologic subtype or grade, which may be present in a larger sample. Thus, 18F-FDG PET/CT is useful for distinguishing malignant from benign lesion but further imaging of dogs with diverse tumors, should establish characteristic SUV value cutoffs for detecting primary and metastatic disease, and distinguishing them from benign lesions.